Systematic review and meta-analysis of women's awareness of obstetric fistula and its determinants in Ethiopia - Melis, Tamirat; Mose, Ayenew (Frontiers in Global Women's Health, 2023)
Background Although obstetric fistula has been extensively eliminated in high-income countries due to comprehensive obstetric health care services, in developing countries including Ethiopia, many women and girls are still silently suffering from obstetric fistula due to early marriage, poor socioeconomic status, lack of access to skilled birth attendants, and limited awareness of obstetric fistula. Objective To determine the magnitude of women's awareness of obstetric fistula and its contributing factors in Ethiopia. Methods To perform this analysis, we strictly adhered to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) recommendations. To evaluate publication bias, we employed an Egger's test and an eye assessment of the funnel plot's symmetry. To look for signs of study heterogeneity, the Cochrane Q-test and I2 statistics were used. A Microsoft Excel spreadsheet was used to extract the data, and STATA version 14 was used to analyze it. Results A total of six studies involving 3,024 women were included. The pooled prevalence of women's awareness of obstetric fistula in Ethiopia was 41.24% (95% CI; 32.94%−49.54%). Urban residence (AOR = 2.32, 95% CI: 1.40–3.85), giving birth at a health institution (AOR = 2.84, 95% CI: 1.92–4.21), having secondary or above educational status (AOR = 3.27, 95% CI: 2.15–4.97), receiving antenatal care follow-up (AOR = 2.73, 95% CI: 1.71–4.35), and participation in pregnant women's conferences (AOR = 4.64, 95% CI: 2.88–7.49) were factors associated with good awareness of obstetric fistula in women in Ethiopia. Conclusion The pooled prevalence of women's awareness of obstetric fistula was low. Urban residence, giving birth at a health institution, having secondary and above educational status, having antenatal care follow-up, and participating in pregnant women's conferences were factors associated with women's awareness of obstetric fistula. Therefore, enhancing women's awareness of obstetric fistula and promoting institutional delivery and antenatal follow-up is recommended. Furthermore, policymakers and stakeholders should empower women and pay particular attention to the neglected but important public health problem that is obstetric fistula.